STUDY OF ADVERSE DRUG REACTIONS OF LINEZOLID IN DRUG RESISTANT TUBERCULOSIS PATIENTS - Susilo, Rinto; Sundhani, Elza; Setyaningsih, Indah; Retnaningsih, Ririn; Nurjanah, Ucu; Endang Ayu Prihatini, Nok (Universitas Muhammadiyah Magelang, 2025)
The estimated number of DR TB patients in Indonesia is increasing. High adverse drug reactions have the potential to affect the success of DR TB patient treatment. Linezolid is one of the drugs in combination with DR TB therapy that has the potential to cause adverse drug reactions in the form of hematological disorders and visual impairment. This study aims to determine the incidence of Linezolid ADRs, including the incidence, severity, and risk factors associated with the occurrence of ADRs. This type of study is observational with a cross-sectional design conducted retrospectively in DR TB patients at the lung clinic of Hospital 'X